Sharing secrets, revealing thoughts and feelings: perceptions about disclosure practices and anonymity in a FB university students' community. (2017) - Sideri, Maria; Kitsiou, Angeliki; Kalloniatis, Christos; Gritzalis, Stefanos
The aim of this study was to identify students' perceptions about personal information disclosure and anonymity in a specific Facebook University Community. The explicit goal of this Community is the sharing of secrets and the revelation of students' deepest thoughts and feelings on high sensitive issues as their erotic or sexual life, leading to information disclosures in various ways. An online survey was conducted and spread through Community's Facebook profile in order to record students' perceptions about the Community and to identify disclosure practices as well as perceived benefits and costs deriving from their participation. Anonymity as expected is valued positively while privacy violations seem to bother less since this is a public Community resulting in a stated comfort about secondary disclosure taking place through reference to persons' physical or other characteristics. This study enhances existing literature on Facebook, by enlightening more facets of personal information disclosure on Facebook students' communities.